2013
DOI: 10.3109/10641963.2013.776568
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Sodium Alginate Oligosaccharides Prevents Salt-Induced Hypertension in Dahl Salt-Sensitive Rats

Abstract: Our results suggest that sodium alginate oligosaccharides attenuate salt-induced hypertension in Dahl S rats not through reducing salt absorption, but probably through a direct action on vascular vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…In addition, it is also documented to attenuate hypertension, associated kidney damage. 10 Therefore, we hypothesize that administration of LvSA may preserve renal function, prevent histological alterations in LA-induced nephrotoxicity with mild chelation and by suppressing oxidative stress. Additionally, LvSA will be evaluated with suitable biochemical and histopathological parameters for its possible Reno protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also documented to attenuate hypertension, associated kidney damage. 10 Therefore, we hypothesize that administration of LvSA may preserve renal function, prevent histological alterations in LA-induced nephrotoxicity with mild chelation and by suppressing oxidative stress. Additionally, LvSA will be evaluated with suitable biochemical and histopathological parameters for its possible Reno protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms involved in antihypertensive effects of AOS were investigated by Moriya et al. (). Subcutaneous administration of AOS (60 mg/day) for 14 days in Dahl S rat fed a high‐salt diet (4% NaCl) almost completely abolished salt‐induced hypertension.…”
Section: Health Beneficial Effects and Potential Aos Applicationsmentioning
confidence: 99%
“…It currently is being evaluated as a treatment for chronic respiratory diseases such as cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD) [48]. Furthermore, Guo et al (2016) found that AOS decreased the expression of Caspase-12, C/EBP homologous protein (CHOP) and Bax while upregulating the expression of anti-apoptotic protein Bcl-2, which are markers for endoplasmic reticulum-mediated apoptosis [51]. Taken together, these results demonstrated that AOS is a promising compound that prevents acute DOX cardiotoxicity via inhibition of oxidative stress and endoplasmic reticulum-mediated apoptosis [51].…”
Section: Pharmaceutical and Biomedical Applicationsmentioning
confidence: 99%
“…Furthermore, Guo et al (2016) found that AOS decreased the expression of Caspase-12, C/EBP homologous protein (CHOP) and Bax while upregulating the expression of anti-apoptotic protein Bcl-2, which are markers for endoplasmic reticulum-mediated apoptosis [51]. Taken together, these results demonstrated that AOS is a promising compound that prevents acute DOX cardiotoxicity via inhibition of oxidative stress and endoplasmic reticulum-mediated apoptosis [51]. Therefore, with the unique properties of AOS and their derivatives, they might be beneficial biomedicine in many diseases.…”
Section: Pharmaceutical and Biomedical Applicationsmentioning
confidence: 99%